Student Efforts in Rural Areas to Face Problems Nahwu Mobile Learning Online - Deviana, Ade Destri; Rusydi, Akhmad; Azizah, Nisfiatul; Muradi, Ahmad; Hafiz, Abdul (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
Online learning that a solution to education during the COVID19 has created a problem for the unprivileged society as limited internet access, but they have kept participating; students made several efforts. This study aims to determine the actions of students living in rural areas in overcoming the problems of online learning nahwu for students of STIQ Amuntai who live in rural areas. This study used a descriptive qualitative approach. The subjects of this study were several students of the IIB PBA STIQ Amuntai. They live in rural areas and settle far from the Amuntai sub-district, South Kalimantan, Indonesia. Data were obtained through interview and documentation techniques with 20 students. The data were analyzed using data reduction, presentation, and conclusion drawing, then data accuracy with the persistence of observation and triangulation. The results of the study are the efforts made by these students in overcoming problems such as unstable signals, lack of focus in studying, low telephone specifications, limited internet quota, difficulty understanding material, little reference material, and boredom, namely: a) going to a place that has a signal (network) stable b) go to a place that is not noisy; c) study in groups on one mobile phone; d) search for free wifi; e) foster self-motivation; d) preparation of materials and independent search of additional literature. Therefore, this study suggests that institutions need to be involved in solving problems related to limited access to offline learning or collaboration with internet network providers.